Crisis de sistema(s) y transiciones del fin del siglo XX en las áreas semiperiféricas del mundo - Harsányi, Iván (Acta Hispanica, 2016)
The nature of the transitions in theseregions of the world (Southern Europe, CentralEastern Europe and Latin America) reflectstheir historical antecedents, the particularities ofthe period when they occured, and the currentbalance of the respective international forces.The distinctive feature of the Central-EasternEuropean transitions is that these changes werenot limited to the transformations of their respectivepolitical regimes, but affected their entiresocioeconomic structure, this is why theyserved as origins of tensions that lasted for variousdecades. In each of these countries, differenttypes of dictatorial or authoritarian regimeswere established in the first half of the 20thcentury, and played a different role in WorldWar II. With the exception of Yugoslavia, theyall took part in the military and economicorganizations of the Eastern block (the WarsawPact, COMECON), within the context of thebipolar system of powers. Due to their semiperipheralcharacter, most of them had limitedopportunities to catch up with the more developedcountries even after the transition, andtheir steps taken in this direction were hesitants.The comparison between their respectivetransitions is further complicated by theirdifferent political-cultural traditions and by theconsequences of the globalization of societies,due to the effects of the serious global economicand financial crisis that unfolded in 2008and is still present nowadays.